Impact of public sector employment changes on local labour markets: evidence for the Brazilian mesoregions from 2003 to 2010 - Loyo, Alexandre de Oliveira Lima; Resende Filho, Moisés de Andrade; Mendes, Vander Lucas (Estudos Econômicos (São Paulo), 2018)
We estimate the parameter of the impact of an increase in the public sector employment on private sector employment in the two terms of President Lula (2003 to 2010), taking the formal labor market in 137 mesoregions and 20 subsectors of economic activity in Brazil. We adapt the instrumental variable method of Faggio and Overman (2014) to a panel data econometric model that allows the impact parameter to vary across the two President Lula’s terms. The results showed that under the contractionary fiscal policy of the Lula’s first term the impact was crowding out, but under the expansionary fiscal policy of the Lula’s second term, the impact was multiplier. Moreover, the change in the public employment affected the sectorial composition of employment in Brazil in the short run, as we found crowding out and multiplier effects for the first and second Lula terms in the tradable goods (industry) and non tradable (construction and services) sectors of the Brazilian economy.